Additive manufacturing applied to the construction industry - Development of earthen-based and cement-based matrices for additive construction - Silva Mondragon, Guido Leonardo (Pontificia Universidad Católica del Perú, 2022)
The application of additive manufacturing technologies for construction has evidenced potential economic, social, and environmental benefits compared to conventional casting procedures. 3D printing for construction is a disruptive technology with the potential for rapid and massive applications making it a feasible alternative for social housing, temporary shelters after disasters, and, recently, extraterrestrial habitats. In this line, this thesis presents the development of earthen-based and cement-based matrices with fresh properties, hardening, and hardened-state properties compatible with this new construction process. First, a medium-scale 3D printing prototype was designed and validated for additive construction applications. The revision of state of the art helps us to define the key properties to design printable matrices: flowability, extrudability, open time, and buildability. Based on these key properties, together with a mechanical evaluation and shrinkage cracking monitoring, printable earthen-based and cement-based matrices were developed. First, the printable capabilities of ecofriendly earthen-based matrices which use potato starch as a natural stabilizer for raw soil mortars aim to obtain 3D printed filaments with adequate fresh and hardenedstates properties. The results indicate that printable earthen-based matrices reinforced with 1 % of sisal fibers by weight of soil and stabilized with aqueous starch gels with concentrations up to 5 % (w/w) showed improved workability and minor cracking and can be used for 3D printing. Then, the thesis presents a methodology based on a set of low-cost experimental tests for the development of cement-based matrices suitable for layer-by-layer deposition. The results of the systematic experimental campaign indicate that yield strength obtained by shear vane tests is a good reference value for proportioning extrudable, pumpable, and buildable concretes. However, special attention has to be given to the binder/fine aggregate weight ratio as low binder contents can lead to clogging of the pumping system. The current research shows four formulations with good printing capabilities obtained after shear vane tests, filament printing tests, and stacking tests. Finally, two medium-scale section walls have been additively manufactured using the optimum concrete validating the proposed methodology.
Keywords: Procesos de manufactura--Productos nuevos; Construcción industrializada; Materiales de construcción--Impresión tridimensional; https://purl.org/pe-repo/ocde/ford#2.00.00